Análise computacional de blocos sobre estacas em concreto armado - Kvas, Cleverson Fernando (2014)
The objective of this research is to study the reinforced concrete’s performance when submitted a centered load to two, three or four pile caps through numerical analysis. The parameters of pre-sizing and loading adopted were based on works by renowned authors on the subject, varying the dimensions of the pillars, pile caps and piles in order to find variations in the stress paths and general behavior of the models. For the pile caps modeling, used the software SAP2000 © 2013, that makes the analysis by the finite element method. For practical purposes, the material behavior was considered linear elastic and the results of interest were the stress paths in their main directions. Made a comparison between developed models and studied in the literature review. It was concluded that the existing analytical models in the literature are more conservative than the numerical models and the spreading of the stress at the base of the pillar differs from the strut and tie method developed by Blévot (1967). Perceives that the geometric variation of the pile caps affected the distribution of the loading over the models, and there was similar behavior between the pile caps of two, three and four piles.